Ti3Al-TiAl laminated composite material as well as preparation method and application thereof
The Ti3Al-TIAL stacked composite material is prepared through the method of vacuum thermal pressure and packs of hot rolling, which solves the problem of insufficient temperature and toughness of TIAL alloy room temperature and the possibility of high temperature performance and the possibility of large-sized production.
Patent Information
- Application Number
- CN202411478537.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing TiAl alloy has low room temperature plasticity and toughness, and while improving room temperature performance, the ultimate use temperature is reduced, which cannot meet the needs of aerospace.
The forging Ti3AL alloys and forging TIAL alloys are used as raw materials. The Ti3Al-Tial layer composite material is prepared through vacuum thermal pressure and hot rolling methods to improve the toughness of its room temperature and maintain high temperature performance.
The room temperature resistance, plasticity and high temperature yield strength of composite materials are effectively improved, and large -sized and large -scale production needs are met, and they have good application prospects.
Smart Images

Figure CN119348247A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laminated composite materials, and particularly relates to a Ti 3 Al-TiAl laminated composite material and preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] TiAl alloy sheets have broad application prospects in the aerospace field due to their low density, high specific strength, good high-temperature oxidation resistance and creep resistance. However, due to the intrinsic brittleness of TiAl alloy, its plasticity and toughness at room temperature are low, which seriously hinders its further development and engineering application. To solve this problem, some scholars have proposed to add soft and tough titanium or titanium alloy to TiAl alloy to prepare titanium alloy-TiAl laminated composite materials to improve the room temperature plasticity and toughness of TiAl alloy and have achieved some research results. However, the limit use temperature of high-temperature titanium alloy is usually 650℃, and the limit use temperature of some short-term high-temperature titanium alloys is difficult to exceed 700℃. Therefore, while this composite material improves the room temperature plasticity and toughness of TiAl alloy, it seriously reduces the limit use temperature of TiAl alloy (the use temperature of TiAl alloy is 750℃~850℃), which cannot meet the use requirements of aerospace.
[0004] High temperature yield strength and high temperature tensile strength are two important indicators for measuring the ultimate use temperature of high temperature materials. Tensile strength refers to the strength at which a material breaks during service; while yield strength refers to the strength limit that a material can withstand before significant plastic deformation occurs. In actual service, high temperature materials have already undergone significant plastic deformation before breaking, and the material has already failed at this point. Therefore, during high temperature service, the yield strength of a material is more critical than its tensile strength.
[0005] For Ti-TiAl laminated composite materials, the yield strength at 800°C is less than 400MPa. Therefore, in order to further improve the ultimate use temperature and high temperature yield strength of the composite material, some scholars used Ti foil and Al foil as raw materials to prepare TiAl laminated composite materials by hot pressing and diffusion. 3 Al-TiAl laminated composite materials. Compared with titanium alloy, Ti 3 Al alloy has lower density. 3 Al is an intermetallic compound. Ti atoms and Al atoms are bonded by covalent bonds. The interatomic bonding force is stronger, so its maximum service temperature is higher, which can effectively improve the service temperature and strength of the composite material.3 Al-TiAl laminated composite materials have many disadvantages: (1) Due to the existence of the Kirkendall effect, the density of the prepared composite material is low, which seriously reduces the mechanical properties of the composite material; (2) The room temperature and high temperature performance of the composite material prepared by this method is not significantly improved. This is mainly because the composite material prepared with Ti foil and Al foil as raw materials has not been alloyed, and the mechanical properties of the matrix material itself are low, so the room temperature and high temperature performance of the material are not significantly improved; (3) Due to the limitations of hot pressing equipment, it is impossible to prepare large-scale composite materials that meet industrial production requirements, which hinders the further development and application of the material. Summary of the invention
[0006] In order to solve the above technical problems, the present invention aims to provide a Ti 3 Al-TiAl laminated composite material and preparation method and application thereof, specifically forged Ti 3 TiAl alloy and forged TiAl alloy were used as raw materials and TiAl was prepared by vacuum hot pressing and jacket hot rolling. 3 Al-TiAl laminated composite materials improve the room temperature plastic toughness of the composite materials and maintain their high high temperature properties (yield strength, tensile strength), meeting the production needs of large size and large batches, and have good application prospects.
[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0008] In a first aspect of the present invention, there is provided a Ti 3 Al-TiAl laminated composite material, specifically: forged Ti 3 Al alloy and forged TiAl alloy are used as raw materials, vacuum hot pressing and jacket hot rolling are carried out to obtain TiAl 3 Al-TiAl laminated composite material.
[0009] Preferably, wrought Ti 3 The nominal chemical composition of the Al alloy is Ti-(20-25)Al-(0-20)X-(0.1-2)Z (at%), where X is a β-phase stabilizing element and Z is a microalloying element;
[0010] The nominal chemical composition of the wrought TiAl alloy is Ti-(40-45)Al-(0.5-10)X-(0.1-2)Z (at%), where X is a β-phase stabilizing element and Z is a microalloying element.
[0011] Further preferably, the β-phase stabilizing element is selected from one or more of Cr, Mn, V, Mo, Nb, and Fe; and the microalloying element is selected from one or more of W, B, and Y.
[0012] The second aspect of the present invention provides a Ti according to the first aspect. 3 The preparation method of the Al-TiAl laminated composite material comprises the following steps:
[0013] S1. Forged Ti 3 Al and forged TiAl alloys were cut to obtain prefabricated slabs of the two alloys, and the prefabricated slabs were mechanically ground and polished to obtain TiAl. 3 Al and TiAl alloy slabs;
[0014] S2, Ti 3 The Al and TiAl alloy slabs are vacuum hot pressed to obtain composite billets;
[0015] S3, welding and hot rolling the composite blank in sequence to obtain a Ti with a sheath 3 Al-TiAl laminated composite material, Ti is obtained after removing the sheath 3 Al-TiAl laminated composite material.
[0016] Preferably, in step S1, the forged Ti 3 The specific preparation method of Al and forged TiAl alloy is as follows: first, Ti 3 Al alloy and TiAl alloy are smelted, the smelted ingots are forged, and then annealed, cooled, and the jacket is removed;
[0017] The vacuum degree of the smelting is 10 -2 Pa~1Pa, power supply power is 95~105kw; number of smelting is 2~4 times;
[0018] The forging temperature is 1000-1500°C; the forging rate is 0.2-0.6 m / min;
[0019] The annealing temperature is 700-950°C;
[0020] The cutting method is wire cutting; the polishing method is selected from mechanical polishing or electrolytic polishing.
[0021] Preferably, in step S1, the Ti 3 The surface roughness of Al and TiAl alloy slabs is Ra6~Ra8.
[0022] Preferably, in step S1, the Ti 3 The Al and TiAl alloy slabs have a length of 50 mm to 500 mm, a width of 50 mm to 500 mm, and a thickness of 0.5 mm to 20 mm.
[0023] Preferably, in step S2, the vacuum hot pressing method is to 3 Al and TiAl alloy slabs are placed in a graphite mold, preferably with TiAl alternately stacked. 3 Al and TiAl alloy slabs, the number of layers is 2n+1, n is 1 to 20 Ti 3 Al alloy slab integer.
[0024] Further preferably, the surface treated Ti 3 The two sides of the alternately stacked Al and TiAl alloy slabs are TiAl alloy.
[0025] Preferably, in step S2, the process conditions of vacuum hot pressing are as follows: the vacuum degree is 10 -2 Pa~1Pa, the heating rate is 5℃ / min~100℃ / min, the hot pressing temperature is 1000℃~1200℃, the hot pressing time is 0.5h~3h, and the hot pressing pressure is 10MPa~100MPa.
[0026] Preferably, in step S3, the composite blank is placed in a stainless steel sheath, and a welding operation is performed to obtain a welded sealed part, and then the welded sealed part is placed in a heating furnace for heating treatment, and then the welded sealed part is placed on a rolling mill for rolling.
[0027] Further preferably, the heat treatment is performed by heating to 1000°C to 1300°C at a heating rate of 5°C / min to 100°C / min, and the heat preservation time is 10min to 180min.
[0028] Further preferably, the rolling rate is 0.1m / s to 3m / s, the deformation per pass is 5% to 25%, the total rolling deformation is 20% to 90%, the return furnace temperature per pass is 1000°C to 1300°C, and the insulation time per pass is 2min to 15min.
[0029] More preferably, the rolled material is subjected to annealing treatment, specifically, the rolled material is placed in a heating furnace at 500° C. to 800° C. for annealing for 0.5 h to 24 h.
[0030] Preferably, in step S3, the method for removing the sheath is a mechanical processing method.
[0031] The third aspect of the present invention provides a Ti according to the first aspect. 3 Application of Al-TiAl laminated composite materials in the field of aerospace materials.
[0032] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:
[0033] (1) The present invention uses forged Ti 3Al alloy and TiAl alloy are used as raw materials, and the matrix material has been alloyed, which can effectively improve the mechanical properties of the composite material; at the same time, pure Ti foil or titanium alloy is replaced with Ti 3 After the Al alloy is formed, the concentration gradient of Al atoms can be effectively reduced, slowing down the migration of Al atoms from TiAl alloy to Ti 3 The diffusion rate of Al alloy diffusion is increased, thereby inhibiting the Kirkendall effect, effectively improving the density of the composite material, thereby improving the mechanical properties of the composite material.
[0034] (2) The vacuum hot pressing process can effectively remove oxygen between layers, avoid oxidation or the formation of oxide inclusions in the interface area of the composite material, and improve the interface bonding strength of the composite material. At the same time, during the sheath hot rolling process, compared with Ti foil or titanium alloy, Ti 3 The flow stress of Al alloy is closer to that of TiAl alloy, which is conducive to the coordinated deformation of the two, thereby reducing the residual stress in the material, preventing the material from cracking, and improving the mechanical properties of the material; on the other hand, Ti 3 The recovery recrystallization temperature of Al is higher than that of pure titanium or titanium alloy, and the structure is more stable. 3 The recrystallized grain growth rate in the Al alloy is low, and the grains obtained after rolling are finer, which can effectively improve the strength of the composite material. Finally, the preparation process of the present invention is simple, the prepared material has high performance, and large-scale industrial production of the material can be realized.
[0035] (3) Ti obtained by the present invention 3 The size of Al-TiAl laminated composite material is (200~1000)mm*(80~500)mm*(1~5)mm, the room temperature tensile strength is 900~1100MPa, the room temperature plasticity is 3%~6%, and the fracture toughness is 35MPa·m 1 / 2 ~50MPa·m 1 / 2 The tensile strength at 800℃ can reach 650~800MPa, the yield strength at 800℃ can reach 600~700MPa, and the plasticity at 800℃ is 20%~30%. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a flow chart for preparing the composite material of the present invention;
[0037] Figure 2 1 is the tensile stress-strain curve of Example 1 and Comparative Example 1 at 800° C., wherein point A and point a are the tensile strength, and point B and point b are the yield strength. DETAILED DESCRIPTION
[0038] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0039] As mentioned above, the composite materials currently prepared have many disadvantages: (1) Due to the existence of the Kirkendall effect, the density of the prepared composite materials is low, which seriously reduces the mechanical properties of the composite materials; (2) The room temperature performance and high temperature performance of the composite materials prepared by this method are not significantly improved. This is mainly because the composite materials prepared with Ti foil and Al foil as raw materials have not been alloyed, and the mechanical properties of the matrix material itself are low, so the room temperature and high temperature performance of the material are not significantly improved; (3) Due to the limitations of hot pressing equipment, it is impossible to prepare large-scale composite materials that meet industrial production requirements, which hinders the further development and application of the material. Therefore, technicians in this field are in urgent need of designing a composite material with good room temperature plasticity and toughness and high temperature performance (tensile strength, yield strength, etc.) that can meet the needs of large-scale and mass production.
[0040] A first typical embodiment of the present invention provides a Ti 3 Al-TiAl laminated composite material, specifically: forged Ti 3 Al alloy and forged TiAl alloy are used as raw materials, vacuum hot pressing and jacket hot rolling are carried out to obtain TiAl 3 Al-TiAl laminated composite material.
[0041] In one or more embodiments of this embodiment, the forged Ti 3 The nominal chemical composition of the Al alloy is Ti-(20-25)Al-(0-20)X-(0.1-2)Z (at%), where X is a β-phase stabilizing element and Z is a microalloying element;
[0042] The nominal chemical composition of the wrought TiAl alloy is Ti-(40-45)Al-(0.5-10)X-(0.1-2)Z (at%), where X is a β-phase stabilizing element and Z is a microalloying element.
[0043] In one or more examples of this embodiment, the β-phase stabilizing element is selected from one or more of Cr, Mn, V, Mo, Nb, and Fe; and the microalloying element is selected from one or more of W, B, and Y.
[0044] A second typical embodiment of the present invention provides a Ti 3 The preparation method of the Al-TiAl laminated composite material comprises the following steps:
[0045] S1. Forged Ti3 Al and forged TiAl alloys were cut to obtain prefabricated slabs of the two alloys, and the prefabricated slabs were mechanically ground and polished to obtain TiAl. 3 Al and TiAl alloy slabs;
[0046] S2, Ti 3 The Al and TiAl alloy slabs are vacuum hot pressed to obtain composite billets;
[0047] S3, welding and hot rolling the composite blank in sequence to obtain Ti with a sheath 3 Al-TiAl laminated composite material, Ti is obtained after removing the sheath 3 Al-TiAl laminated composite material.
[0048] In one or more examples of this implementation mode, in step S1, the cutting method is wire cutting; and the polishing method is selected from one of mechanical polishing and electrolytic polishing.
[0049] In one or more examples of this embodiment, in step S1, the Ti 3 The surface roughness of Al and TiAl alloy slabs is Ra6~Ra8.
[0050] In one or more examples of this embodiment, in step S1, the Ti 3 The Al and TiAl alloy slabs have a length of 50 mm to 500 mm, a width of 50 mm to 500 mm, and a thickness of 0.5 mm to 20 mm.
[0051] In one or more embodiments of this embodiment, in step S2, the vacuum hot pressing method is to 3 Al and TiAl alloy slabs are placed in a graphite mold, preferably with TiAl alternately stacked. 3 Al and TiAl alloy slabs, the number of layers is 2n+1, n is 1 to 20 Ti 3 Al alloy slab integer.
[0052] In one or more embodiments of this embodiment, the surface treated Ti 3 The two sides of the alternately stacked Al and TiAl alloy slabs are TiAl alloy.
[0053] In one or more examples of this embodiment, in step S2, the process conditions of the vacuum hot pressing are specifically: the vacuum degree is 10 -2 Pa~1Pa, the heating rate is 5℃ / min~100℃ / min, the hot pressing temperature is 1000℃~1200℃, the hot pressing time is 0.5h~3h, and the hot pressing pressure is 10MPa~100MPa.
[0054] In one or more examples of this embodiment, in step S3, the composite blank is placed in a stainless steel sheath, and a welding operation is performed to obtain a welded sealed part, and then the welded sealed part is placed in a heating furnace for heat treatment, and then the welded sealed part is placed on a rolling mill for rolling.
[0055] In one or more examples of this embodiment, the heat treatment is performed at a heating rate of 5°C / min to 100°C / min to a temperature of 1000°C to 1300°C, and the heat preservation time is 10min to 180min.
[0056] In one or more embodiments of this implementation, the rolling rate is 0.1m / s~3m / s, the deformation per pass is 5%~20%, the total rolling deformation is 20%~90%, the return furnace temperature per pass is 1000℃~1300℃, and the insulation time per pass is 2min~10min.
[0057] In one or more examples of this implementation mode, the rolled material is subjected to annealing treatment, specifically, the rolled material is placed in a heating furnace at 500° C. to 800° C. for annealing for 0.5 h to 24 h.
[0058] In one or more examples of this implementation mode, in step S3, the method for removing the sheath is a mechanical processing method.
[0059] A third typical embodiment of the present invention provides a Ti 3 Application of Al-TiAl laminated composite materials in the field of aerospace materials.
[0060] The present invention proposes to use forged Ti 3 TiAl alloy and forged TiAl alloy were used as raw materials and TiAl was prepared by vacuum hot pressing and jacket hot rolling. 3 Al-TiAl laminated composite material. The main purpose is to improve the room temperature plasticity and toughness of TiAl alloy and maintain its high high temperature performance. 3 Al alloy and TiAl alloy are obtained by smelting and forging methods. After alloying the matrix material, the mechanical properties of the composite material can be effectively improved. 3 When Al and TiAl alloys are used as raw materials, the concentration gradient of Al atoms can be effectively reduced, thereby avoiding the Kirkendall effect to a certain extent and improving the mechanical properties of the composite material; finally, the vacuum hot pressing and jacket hot rolling methods are suitable for industrial production and meet the production needs of large sizes and large batches. At the same time, during the rolling process, a larger rolling force can improve the Ti 3The bonding strength of Al alloy and TiAl alloy. The dynamic recovery recrystallization process during rolling can effectively refine the grains, produce fine grain strengthening, and improve the plasticity, toughness and strength of the composite material.
[0061] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0062] Example 1 :This embodiment provides a Ti 3 Al-TiAl laminated composite material and preparation method thereof
[0063] (1) Titanium sponge, aluminum bean, Al-V, Al-Nb and Al-Y master alloys were selected, and TiAl alloy with nominal composition of Ti-43Al-9V-0.3Y (at.%) and TiAl alloy with nominal composition of Ti-24Al-15Nb-0.2Y (at.%) were respectively prepared. 3 The Al alloy was melted in a vacuum induction suspension melting furnace. The melting vacuum was 10 -2 Pa, the power supply during smelting is 100kw (2500-2600℃), and each ingot is smelted 3 times. Then the two ingots are sealed with stainless steel for sheath forging. The forging temperature is 1200℃, the deformation is 80%, and the forging rate is 0.5m / min. The forged material is annealed at 900℃ for 12h, and then the furnace is cooled to room temperature. The sheath is removed by wire cutting to obtain the forged TiAl alloy and forged Ti 3 Al alloy.
[0064] (2) Forged TiAl alloy and Ti 3 The Al alloy was subjected to wire cutting, chamfering and surface polishing to obtain a slab with a size of 120 mm × 80 mm × 2 mm, a fillet radius of 2 mm and a surface finish of Ra8.
[0065] (3) Three TiAl alloy slabs and two Ti 3 Al alloy slabs were alternately placed in graphite molds, with TiAl alloy on both sides. The vacuum furnace was evacuated to 0.1 Pa, and then the furnace temperature was raised to 1100°C at a heating rate of 50°C / min. Then a pressure of 30MPa was applied to the sample and maintained for 1h. After the hot pressing was completed, the sample was cooled to room temperature with the furnace to obtain a composite blank.
[0066] (4) The composite blank is welded and sealed with 304 stainless steel.
[0067] (5) Place the welded billet into a heating furnace, and then heat the furnace to 1150°C at a heating rate of 20°C / min. After keeping the temperature at this temperature for 30 minutes, place the composite billet on the rolling mill for rolling. The rolling rate is 0.5m / min, the deformation amount per pass is 20%, the total deformation amount is 80%, the return temperature per pass is 1150°C, and the holding time per pass is 8 minutes. The rolled material is placed in a heating furnace at 750°C for 6 hours, and then cooled to room temperature with the furnace.
[0068] (6) Remove the sheath by mechanical processing to obtain a Ti with a size of 480 mm × 100 mm × 2 mm 3 Al-TiAl laminated composite material.
[0069] Example 2 :This embodiment provides a Ti 3 Al-TiAl laminated composite material and preparation method thereof
[0070] (1) Select titanium sponge, aluminum beans, B 4 C, Al-Nb, Al-Y, and Al-W master alloys were used to characterize the TiAl alloy with a nominal composition of Ti-44Al-8.5Nb-0.2W-0.1B-0.1Y (at.%) and the TiAl alloy with a nominal composition of Ti-22Al-12Nb-0.2Y (at.%). 3 The Al alloy was melted in a vacuum induction suspension melting furnace. The melting vacuum was 10 -2 Pa, the power supply during smelting is 100kw (2500~2600℃), and each ingot is smelted 3 times. Then, two ingots are sealed with stainless steel for jacket forging. The forging temperature of TiAl alloy is 1250℃, Ti 3 The forging temperature of the Al alloy was 1200°C. The deformation of both alloys was 80%, and the forging rate was 0.5 m / min. The forged materials were annealed at 900°C for 12 h and then furnace cooled to room temperature. The sheath was removed by wire cutting to obtain the forged TiAl alloy and forged Ti 3 Al alloy.
[0071] (2) Forged TiAl alloy and Ti 3 The Al alloy was subjected to wire cutting, chamfering and surface polishing to obtain a slab with a size of 80 mm × 60 mm × 2 mm, a fillet radius of 2 mm and a surface finish of Ra8.
[0072] (3) Four TiAl alloy slabs and three Ti 3Al alloy slabs were alternately placed in graphite molds, with TiAl alloy on both sides. The vacuum furnace was evacuated to 0.1 Pa, and then the furnace temperature was raised to 1050°C at a heating rate of 50°C / min. Then a pressure of 30MPa was applied to the sample and maintained for 1h. After the hot pressing was completed, the sample was cooled to room temperature with the furnace to obtain a composite blank.
[0073] (4) The composite blank is welded and sealed with 304 stainless steel.
[0074] (5) Place the welded billet in a heating furnace, and then heat the furnace to 1200°C at a heating rate of 20°C / min. After keeping the temperature at this temperature for 30 minutes, place the composite billet on the rolling mill for rolling. The rolling rate is 0.5m / min, the deformation amount per pass is 15%, the total deformation is 80%, the return temperature per pass is 1200°C, and the holding time per pass is 10 minutes. Place the rolled material in a heating furnace at 800°C for 6 hours, and then cool it to room temperature with the furnace.
[0075] (6) Remove the sheath by machining to obtain a Ti with a size of 320 mm × 80 mm × 2.5 mm 3 Al-TiAl laminated composite material.
[0076] Comparative Example 1 :This comparative example provides a Ti-TiAl laminated composite material and a preparation method thereof
[0077] (1) Titanium sponge, aluminum bean, Al-V and Al-Y master alloys were selected to melt TiAl alloy with nominal composition of Ti-43Al-9V-0.3Y (at.%) and titanium alloy with nominal composition of Ti-6Al-4V (wt.%) in a vacuum induction levitation melting furnace. The melting vacuum was 10 -2 Pa, the power supply during smelting is 100kw (2500-2600℃), and each ingot is smelted 3 times. Subsequently, the TiAl alloy is welded with stainless steel for sheath forging. The forging temperature of the TiAl alloy is 1200℃, and the forging temperature of the titanium alloy is 960℃. The deformation of both alloys is 80%, and the forging rate is 0.5m / min. The forged TiAl is annealed at 900℃ for 12h, and the titanium alloy is annealed at 600℃ for 12h. After annealing, the two materials are cooled to room temperature with the furnace. The sheath is removed by wire cutting to obtain the forged TiAl alloy and forged titanium alloy.
[0078] (2) The forged TiAl alloy and titanium alloy were subjected to wire cutting, chamfering and surface polishing to obtain a slab with a size of 120 mm × 80 mm × 2 mm, a fillet radius of 2 mm and a surface finish of Ra8.
[0079] (3) Three TiAl alloy slabs and two titanium alloy slabs were placed alternately in a graphite mold, with TiAl alloy on both sides. The vacuum furnace was evacuated to 0.1 Pa, and then the furnace temperature was raised to 1100°C at a heating rate of 50°C / min. A pressure of 30 MPa was then applied to the sample and maintained for 1 hour. After the hot pressing was completed, the sample was cooled to room temperature with the furnace to obtain a composite blank.
[0080] (4) The composite blank is welded and sealed with 304 stainless steel.
[0081] (5) Place the welded billet in a heating furnace, and then heat the furnace to 1200°C at a heating rate of 20°C / min. After keeping the temperature at this temperature for 30 minutes, place the composite billet on the rolling mill for rolling. The rolling rate is 0.5m / min, the deformation amount per pass is 20%, the total deformation is 80%, the return temperature per pass is 1200°C, and the holding time per pass is 8 minutes. The rolled material is placed in a heating furnace at 700°C for 6 hours, and then cooled to room temperature with the furnace.
[0082] (6) The sheath is removed by mechanical processing to obtain a Ti-TiAl laminated composite material with a size of 480 mm × 100 mm × 2 mm.
[0083] Comparative Example 2 :This comparative example provides a Ti-TiAl laminated composite material and a preparation method thereof
[0084] (1) Select titanium sponge, aluminum beans, B 4 C, Al-Nb, Al-V, Al-Y, Al-W and Al-Y master alloys were melted in a vacuum induction levitation melting furnace for TiAl alloy with nominal composition of Ti-44Al-8.5Nb-0.2W-0.1B-0.1Y (at.%) and titanium alloy with nominal composition of Ti-6Al-4V (wt.%). The melting vacuum was 10 -2 Pa, the power supply during smelting is 100kw (2500-2600℃), and each ingot is smelted 3 times. Subsequently, the TiAl alloy is welded with stainless steel for sheathing forging. The forging temperature of the TiAl alloy is 1250℃, and the forging temperature of the titanium alloy is 960℃. The deformation of both alloys is 80%, and the forging rate is 0.5m / min. The forged TiAl is annealed at 960℃ for 12h, and the titanium alloy is annealed at 600℃ for 12h. After annealing, the two materials are cooled to room temperature with the furnace. The sheath is removed by wire cutting to obtain the forged TiAl alloy and forged titanium alloy.
[0085] (2) The forged TiAl alloy and titanium alloy were subjected to wire cutting, chamfering and surface polishing to obtain a slab with a size of 80 mm × 60 mm × 2 mm, a fillet radius of 2 mm and a surface finish of Ra8.
[0086] (3) Four TiAl alloy slabs and three titanium alloy slabs were placed alternately in a graphite mold, with TiAl alloy on both sides. The vacuum furnace was evacuated to 0.1 Pa, and then the furnace temperature was raised to 1100°C at a heating rate of 50°C / min. A pressure of 30 MPa was then applied to the sample and maintained for 1 hour. After the hot pressing was completed, the sample was cooled to room temperature with the furnace to obtain a composite blank.
[0087] (4) The composite blank is welded and sealed with 304 stainless steel.
[0088] (5) Place the welded billet into a heating furnace, and then heat the furnace to 1250°C at a heating rate of 20°C / min. After keeping the temperature at this temperature for 30 minutes, place the composite billet on the rolling mill for rolling. The rolling rate is 0.5m / min, the deformation amount per pass is 15%, the total deformation amount is 80%, the return temperature per pass is 1250°C, and the holding time per pass is 10 minutes. Place the rolled material in a heating furnace at 750°C for 6 hours, and then cool it to room temperature with the furnace.
[0089] (6) The sheath is removed by mechanical processing to obtain a Ti-TiAl laminated composite material with a size of 320 mm × 80 mm × 2.5 mm.
[0090] Comparative Example 3 :This comparative example provides a Ti 3 Al-TiAl laminated composite material and preparation method thereof
[0091] (1) Six pieces of industrial Ti foils with a size of 50 mm*50 mm*220 μm and five pieces of industrial Al foils with a size of 50 mm*50 mm*200 μm were cleaned with a mixed solution of 10% NaOH and 15% HF to remove the oxide scale. The foils after the oxide scale removal were then placed in anhydrous ethanol, cleaned with ultrasonic waves and dried.
[0092] (2) The cleaned Ti foil and Al foil are alternately placed in a hot pressing furnace for hot pressing to obtain a Ti-Al composite material. The hot pressing process parameters are: 500℃ / 60min / 10 -2 Pa.
[0093] (3) Put the Ti-Al composite material into a hot pressing furnace and continue hot pressing to obtain Ti-Al 3 Ti composite material. Hot pressing process parameters are: 1200℃ / 30min / 10 -2 Pa.
[0094] (4) Ti-Al 3 The Ti composite material is placed in a hot pressing furnace for densification treatment to obtain a Ti-Al composite with a high density. 3 Ti composite material. Densification process parameters are: 1300℃ / 40MPa / 2h / 10 -2 Pa.
[0095] (5) The Ti-Al 3 The Ti composite material was placed in a hot press furnace for double-step heat treatment and then cooled to room temperature to obtain a Ti composite material with a size of 50 mm*50 mm*2.2 mm. 3 Al-TiAl laminated composite material. The process parameters of double-step heat treatment are: ① 1300℃ / 12h / 10 -2 Pa; ②1350℃ / 10min / 10 -2 Pa.
[0096] Test Example 1 :
[0097] This test example tests the relevant properties of the composite materials obtained in Examples 1 to 2 and Comparative Examples 1 to 3, as shown in Table 1:
[0098] Table 1
[0099]
[0100] From the data in Table 1, it can be seen that the Ti prepared by the present invention 3 The room temperature tensile strength of Al-TiAl laminated composite materials is 900-1100MPa, the room temperature plasticity is 3%-6%, and the fracture toughness is 35MPa·m 1 / 2 ~50MPa·m 1 / 2 The tensile strength at 800℃ can reach 650~800MPa, the yield strength at 800℃ can reach 600~700MPa, and the plasticity at 800℃ is 20%~30%.
[0101] Compared with Comparative Examples 1-2, the room temperature tensile strength of Examples 1-2 is close to that of Comparative Examples, and the room temperature plasticity, fracture toughness and 800℃ plasticity are slightly lower than those of Comparative Examples 1-2. However, the 800℃ tensile strength and yield strength of Examples 1-2 are much higher than those of Comparative Examples 1-2 (230-300MPa higher). 3 After Al alloying, the bonding mode of Ti atoms and Al atoms changes from solid solution strengthening to covalent bonding, which can effectively improve the interatomic bonding force and elastic modulus, thereby improving the operating temperature and strength of the composite material.
[0102] Compared with Comparative Example 3, the performance indicators of Examples 1 to 2 are much higher than those of Comparative Example 3. This is because the raw materials in Comparative Example 3 are Ti foil and Al foil, which have not been alloyed; at the same time, during the hot pressing process, the atomic diffusion rate of Al is fast, the concentration gradient is large, and it is easy to form holes (Kirkendall effect), which reduces the mechanical properties of the composite material. In terms of preparation method, the composite material prepared by jacket hot rolling will improve its interface bonding strength under the action of huge rolling force; the matrix material will also undergo dynamic recovery recrystallization during the rolling process, refine the microstructure, and improve the mechanical properties of the composite material.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A Ti3Al-TiAl laminated composite material, characterized in that: Specifically, forged Ti3Al alloy and forged TiAl alloy are used as raw materials, vacuum hot pressing and jacket hot rolling are carried out to obtain Ti3Al-TiAl laminated composite material.
2. The Ti3Al-TiAl laminated composite material according to claim 1, characterized in that: The nominal chemical composition of the wrought Ti3Al alloy is Ti-(20-25)Al-(0-20)X-(0.1-2)Z (at%), and the nominal chemical composition of the wrought TiAl alloy is Ti-(40-45)Al-(0.5-10)X-(0.1-2)Z (at%), wherein X is a β-phase stabilizing element and Z is a microalloying element.
3. The Ti3Al-TiAl laminated composite material according to claim 2, characterized in that: The β-phase stabilizing element is selected from one or more of Cr, Mn, V, Mo, Nb, and Fe; and the microalloying element is selected from one or more of W, B, and Y.
4. A method for preparing the Ti3Al-TiAl laminated composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Cutting the forged Ti3Al and the forged TiAl alloy to obtain prefabricated slabs of the two alloys, and mechanically grinding and polishing the prefabricated slabs to obtain Ti3Al and TiAl alloy slabs; S2, vacuum hot pressing the Ti3Al and TiAl alloy slabs to obtain a composite blank; S3, welding and hot rolling the composite blank in sequence to obtain a Ti3Al-TiAl laminated composite material with a sheath, and removing the sheath to obtain the Ti3Al-TiAl laminated composite material.
5. The preparation method according to claim 4, characterized in that: In step S1, the specific preparation method of the forged Ti3Al and the forged TiAl alloy is: firstly smelting the Ti3Al alloy and the TiAl alloy, forging the ingots obtained by smelting, and then annealing, cooling, and removing the sheath to obtain the ingots; The vacuum degree of the smelting is 10 -2 Pa~1Pa, power supply power is 95~105kw; number of smelting is 2~4 times; The forging temperature is 1000-1500°C; the forging rate is 0.2-0.6 m / min; The annealing temperature is 700-950°C; The cutting method is wire cutting; the polishing method is selected from mechanical polishing or electrolytic polishing.
6. The preparation method according to claim 4, characterized in that: In step S1, the surface roughness of the Ti3Al and TiAl alloy slabs is Ra6-Ra8; The Ti3Al and TiAl alloy slabs have a length of 50 mm to 500 mm, a width of 50 mm to 500 mm, and a thickness of 0.5 mm to 20 mm.
7. The preparation method according to claim 4, characterized in that: In step S2, the vacuum hot pressing is carried out by placing the surface treated Ti3Al and TiAl alloy slabs in a graphite mold, preferably alternately stacking the Ti3Al and TiAl alloy slabs, the number of layers being 2n+1, where n is an integer of 1 to 20 Ti3Al alloy slabs.
8. The preparation method according to claim 7, characterized in that: The two sides of the alternately stacked Ti3Al and TiAl alloy slabs after surface treatment are TiAl alloy.
9. The preparation method according to claim 4, characterized in that: In step S2, the process conditions of vacuum hot pressing are as follows: the vacuum degree is 10 -2 Pa~1Pa, heating rate is 5℃ / min~100℃ / min, hot pressing temperature is 1000℃~1200℃, hot pressing time is 0.5h~3h, hot pressing pressure is 10MPa~100MPa; Preferably, in step S3, the composite blank is placed in a stainless steel sheath, a welding operation is performed to obtain a welded seal, and then the welded seal is placed in a heating furnace for heating treatment, and then the welded seal is placed on a rolling mill for rolling; Further preferably, the heating treatment is heating to 1000°C to 1300°C at a heating rate of 5°C / min to 100°C / min, and the holding time is 10min to 180min; Further preferably, the rolling rate is 0.1m / s to 3m / s, the deformation amount of each pass is 5% to 25%, the total rolling deformation amount is 20% to 90%, the return temperature of each pass is 1000°C to 1300°C, and the holding time of each pass is 2min to 15min; Further preferably, the rolled material is subjected to annealing treatment, specifically, the rolled material is placed in a heating furnace at 500° C. to 800° C. for annealing for 0.5 h to 24 h; Preferably, in step S3, the method for removing the sheath is a mechanical processing method.
10. Use of the Ti3Al-TiAl laminated composite material according to any one of claims 1 to 3 in the field of aerospace materials.
Citation Information
Patent Citations
Silicon carbide fiber reinforced titanium aluminum matrix composite and making method thereof
CN103879065A
Method for manufacturing TiAl / Ti alloy laminated composite plates in preheating pressing compositing and wrapping hot rolling manner
CN105080999A
HOT FORGING TYPE TiAl-BASED ALLOY AND PRODUCTION METHOD THEREOF
JP2015151612A